1997
DOI: 10.3989/gya.1997.v48.i2.772
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of BHA, BHT and TBHQ examined with Miller's test

Abstract: RESUMENActividad antioxidante de BHA, BHT y TBHQ examinada con el test de l\/liller. KEY-WORDS: Antioxidant activity -Butylated ¡lydroxyaniso-le (BHA) -Butylated hydroxytoluene (BHT) -Tertiary butyl hydroquinone (TBHQ) -Miller's test.En experimentos modelos usando el test de Miller, a 5ml de emulsión se añadió 25, 12.5, 6.25 y S.ISpg de BHA, BHT y TBHQ. Las relaciones inhibitorias (IR) para el BHA y BHT fueron similares. IR para TBHQ fue más baja que para BHA y BHT con niveles de adición del 6.25 y 3.13. Esto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…Hexadecane identified in methanol, chloroform, and ethyl acetate extracts is reported for antibacterial as well as antioxidant activities [39]. Butyl hydroxyl toluene, an excellent antioxidant, contributed 9.45% to the diethyl ether extract [40]. A variant of phytol, 3,7,11,15-tetramethyl-2-hexadecen-1-ol has contributed about 2.73-9.5% in acetone, chloroform and diethyl ether extract.…”
Section: Gc-hrms Analysis Of Crude Organic Extracts Of C Emersonii Kmentioning
confidence: 99%
“…Hexadecane identified in methanol, chloroform, and ethyl acetate extracts is reported for antibacterial as well as antioxidant activities [39]. Butyl hydroxyl toluene, an excellent antioxidant, contributed 9.45% to the diethyl ether extract [40]. A variant of phytol, 3,7,11,15-tetramethyl-2-hexadecen-1-ol has contributed about 2.73-9.5% in acetone, chloroform and diethyl ether extract.…”
Section: Gc-hrms Analysis Of Crude Organic Extracts Of C Emersonii Kmentioning
confidence: 99%
“…Antioxidant activity was expressed by inhibitory ratio as follows, according to the formula used by Karamac and Amarowicz (1997):…”
Section: Antioxidant Activity Measurementmentioning
confidence: 99%
“…In addition, the antioxidative effects of ascorbic acid and ascorbyl palmitate in the O/W emulsions have been fully studied (Van Ruth et al 1999;Liu and Yang 2008;Mosca et al 2008;Watanabe et al 2010;Yang et al 2011). Previous studies have also revealed that tert-butyl hydroquinone (TBHQ) acted effectively as the free radical scavenging agents in emulsions (Karamac and Amarowicz 1997;Kishk and Al-Sayed 2007;Alamed et al 2009). …”
Section: Introductionmentioning
confidence: 99%